A built‐in surface‐enhanced Raman scattering‐active microneedle for sampling in vivo and surface‐enhanced Raman scattering detection ex vivo of NO. (14th August 2018) - Han, Shuyan; Sun, Jie; Wang, Jieyu; Qian, Weiping; Dong, Jian
Abstract: For sampling in vivo and surface‐enhanced Raman scattering (SERS) detection ex vivo, a built‐in SERS‐active microneedle is fabricated by adsorbing gold nanoshells (GNSs; as built‐in SERS‐active materials) in a corroded groove on an acupuncture needle. 3, 4‐diaminobenzene‐thiol adsorbed on the GNSs is used as a selective SERS probe to detect nitric oxide (NO). The SERS‐active microneedles take SERS probes into the tissues of living mice with minimal invasion to react with NO selectively and then they are pulled out for direct and rapid SERS detection without any pretreatment steps or tedious operations. The built‐in SERS‐active microneedle would become a versatile platform for sampling in vivo and SERS detection ex vivo, taking SERS beyond culture cells to living animals. Abstract : A built‐in SERS‐active microneedle has been developed for minimally invasive and selective sampling in vivo and direct and rapid SERS detection ex vivo of NO. After being inserted into tissues with minimal invasion, the SERS‐active microneedle would selectively respond target molecules such as NO, that is, using the SERS‐active microneedles, minimally invasive and selective sampling in vivo would be achieved. After being pulled out, the SERS‐active microneedle can be used for collecting SERS spectra directly, that is, using the SERS‐active microneedles, direct and rapid SERS detection ex vivo would be achieved as well.